Multifunctional dyeing and finishing of polyester with Sericin and Basic dyes. Issue 3 (4th March 2017) - Chaudhary, Harshita; Gupta, Deepti; Gupta, Charu
Abstract : Sericin, a natural biopolymer, is known for its various qualities such as excellent oxygen permeability, antioxidant action, moisture-regulating ability, protection from ultraviolet (UV) radiation and microbes and wound healing properties. It, however, has no direct affinity for textiles. In this study, the surface of a polyester fabric was functionalized and treated with sericin to improve its multifunctional properties and enhance its dyeability with basic dyes. The basic dye uptake of polyester after pre-irradiation treatment was observed to increase considerably in comparison to control. The process conditions for dyeing of irradiated polyester with basic dyes (methylene blue, malachite green and rhodamine B) were observed to be 100 °C, 60 min. Sericin application on irradiated samples further enhanced the basic dye uptake with addition of a yellowish tint to the samples. Sericin application was found to enhance the moisture regain (MR) and radical scavenging activity (RSA) of PET. Higher values of MR, RSA were observed for 0.25% shade basic dyed samples than samples dyed with 2% shade. Wash fastness of dyed samples was observed to be good. Sericin-treated basic dyed samples exhibited antimicrobial activity against S. aureus . An enhancement in zone diameter was observed, with increase in dye concentration from 0.25 to 2%. Maximum value of ZOI (16.5–17 mm) was seen in samples dyed with 1–2% shade. Leaching effect was observed in the zone surrounding the sample due to the diffusion of active dye in the agar medium. Static behaviour of sericin-treated samples was also seen to improve. Sericin finish applied was observed to be durable.